The impact of organisational restructuring on perceptions of trustworthiness - Neville Bews; Tina Uys (SA Journal of Industrial Psychology, 2002)
An opportunity recently arose in a South African organisation currently undergoing drastic structural changes to assess the effects of these changes on the trust relationship between employees and those to whom these employees report. Two studies form the focus of this article. The first one was undertaken prior to the announcement of the restructuring programme. Some 13 months after the restructuring was announced and 10 months after it had commenced, a similar study focusing on trust was undertaken. In this paper the major findings of the two studies on the trust relationship in the organisation are compared. Opsomming Die geleentheid het onlangs ontstaan om die effek van hierdie veranderinge op die vertrouensverhouding tussen werknemers en diegene aan wie hulle rapporteer binne ‘n Suid-Afrikaanse organisasie wat tans drastiese strukturele veranderinge ondergaan, te beoordeel. Hierdie artikel fokus op twee studies. Die eerste een is onderneem net voor die aankondiging van die herstruktureringsprogram. Ongeveer 13 maande na die herstrukturering aangekondig is en tien maande na dit ‘n aanvang geneem het, is ‘n soortgelyke studie oor die vertrouensverhouding onderneem. In hierdie artikel word die belangrikste bevindings van die twee studies met betrekking tot die vertrouensverhouding vergelyk en die resultate bespreek.